2020
DOI: 10.1371/journal.pone.0241273
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive analysis of Thoroughbred horses born in Victoria, Australia, in 2010; barriers to entering training and outcomes on exiting training and racing

Abstract: The reasons for Thoroughbred (TB) horses not entering training or exiting the racing industry, are of interest to regulators, welfare groups and the broader community. Speculation about the outcomes of these horses threatens the community acceptance, or social license, of the TB breeding and racing industries. A representative survey of the 2010 Victorian born TB foal crop was used to determine the outcomes and reasons for exit for horses that had not entered training, or had exited training and racing by eigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 12 publications
4
24
0
Order By: Relevance
“…Previous Australian and New Zealand studies [ 7 , 22 ] reported that the majority of retirements were voluntary in nature, often due to poor performance or owner requests, which is similar to the findings reported in this study. This relatively consistent age of retirement together with the majority of horses retiring for voluntary reasons suggests the decision to retire is not entirely depended on biological or physiological effects, rather it is due to a conflation of factors including horse performance and other industry-level effects.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Previous Australian and New Zealand studies [ 7 , 22 ] reported that the majority of retirements were voluntary in nature, often due to poor performance or owner requests, which is similar to the findings reported in this study. This relatively consistent age of retirement together with the majority of horses retiring for voluntary reasons suggests the decision to retire is not entirely depended on biological or physiological effects, rather it is due to a conflation of factors including horse performance and other industry-level effects.…”
Section: Discussionsupporting
confidence: 89%
“…This finding shows that regulators should focus their traceability efforts on TBs over five-years of age that had not raced or trialled in the last six months. While the age of retirement for females agrees with an earlier Australian study investigating the 2010 Victorian foal crop, males in this study were slightly older at the time of retirement [ 7 ].…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations